British Counterinsurgency - Newsinger, John.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
British Counterinsurgency challenges the British Army's claim to counterinsurgency expertise. It provides well-written, accessible and up-to-date accounts of the post-1945 campaigns in Palestine, Malaya, Kenya, Cyprus, South Yemen, Dhofar, Northern Ireland and more recently in Iraq and Afghanistan.
Keywords: Military history; Great Britain—History.; World politics; History, Modern; Politics and war; History of Military; History of Britain and Ireland; Political History; Modern History; Military and Defence Studies